The Slavic Akathistos Hymn Poetic Elements of the Byzantine Text and Its Old Church Slavonic Translation - Gove, Antonina F. (Slavistische Beitraege, 1988)
This work offers a detailed analysis of the Slavic translation of a sixth-century Greek liturgical poem that is representative of the poetic genius of the best of the Byzantine melodes. The immediate goal has been to discover to what degree the poetic elements of the original text were reproduced in the translation. The analysis illuminates the question of the quality of the Slavic translations of Byzantine liturgical hymns.